2013
DOI: 10.1161/jaha.112.003277
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase‐4 Inhibitors Attenuate Endothelial Function as Evaluated by Flow‐Mediated Vasodilatation in Type 2 Diabetic Patients

Abstract: BackgroundEndothelial dysfunction is an independent predictor for cardiovascular events in patients with type 2 diabetes (T2DM). Glucagon like peptide‐1 (GLP‐1) reportedly exerts vasodilatory actions, and inhibitors of dipeptidyl peptidase‐4 (DPP‐4), an enzyme‐degrading GLP‐1, are widely used to treat T2DM. We therefore hypothesized that DPP‐4 inhibitors (DPP‐4Is) improve endothelial function in T2DM patients and performed 2 prospective, randomized crossover trials to compare the DPP‐4I sitagliptin and an α‐gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 39 publications
2
93
1
1
Order By: Relevance
“…1,6 Additionally, DPP-4 inhibition with vildagliptin 14 potentiates endothelium-dependent vasodilation in response to acetylcholine, whereas others have reported that sitagliptin and alogliptin attenuated endothelial function based on changes in flow-mediated vasodilation in patients with type 2 diabetes mellitus. 15 These vascular findings have been implicated as a potential mechanism for augmented sympathetic activity that could have played a role in the increase in HF hospitalizations in the SAVOR TIMI 53 trial. 3,16 All of the aforementioned studies evaluating the hemodynamic and physiological responses to coadministered higher dose ACE inhibitors and DPP-4 inhibitors were performed using either acute or short-term study designs.…”
Section: Discussionmentioning
confidence: 97%
“…1,6 Additionally, DPP-4 inhibition with vildagliptin 14 potentiates endothelium-dependent vasodilation in response to acetylcholine, whereas others have reported that sitagliptin and alogliptin attenuated endothelial function based on changes in flow-mediated vasodilation in patients with type 2 diabetes mellitus. 15 These vascular findings have been implicated as a potential mechanism for augmented sympathetic activity that could have played a role in the increase in HF hospitalizations in the SAVOR TIMI 53 trial. 3,16 All of the aforementioned studies evaluating the hemodynamic and physiological responses to coadministered higher dose ACE inhibitors and DPP-4 inhibitors were performed using either acute or short-term study designs.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is unlike that lansoprazole influenced the decrease of these lipids levels, because it is reported that PPI therapy for 3 months significantly increased (but not decreased) TC and LDL-C levels with no change of HDL-C in patients with type 2 diabetes [25]. On the other hand, it is reported that alogliptin can reduce LDL-C levels [26][27][28], although these levels did not change in some studies [29,30]. Recently, Ayaori et al reported that alogliptin significantly reduced TC, LDL-C, and HDL-C (but not TG), and that it significantly deceased HDL-C, even when compared with sitagliptin [28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is reported that alogliptin can reduce LDL-C levels [26][27][28], although these levels did not change in some studies [29,30]. Recently, Ayaori et al reported that alogliptin significantly reduced TC, LDL-C, and HDL-C (but not TG), and that it significantly deceased HDL-C, even when compared with sitagliptin [28]. Thus, we speculate that decrease of TC, LDL-C, and HDL-C which were observed in this study was probably associated with the effect of alogliptin, although the precise mechanism is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind study on patients with diabetes, treatment with vidagliptin for 4 weeks improved forearm blood flow in response to intra-arterially delivered acetylcholine [164]. On the contrary, other studies measuring FMD of the brachial artery have shown diametrically opposite results, suggesting that sitagliptin and alogliptin actually seem to worsen flow-mediated dilation (FMD) when used to treat diabetic patients [165]. At present, clinical evidence supporting the vascular protective effects of gliptins is uncertain, given the relatively short follow-up [166][167][168].…”
Section: How Conventional Diabetic Treatments May Ameliorate Endothelmentioning
confidence: 99%